The Mutual Influence of Therapy Group Members' Hope and Depressive Symptoms. (February 2016) - Kivlighan, D. Martin; Paquin, Jill D.; Hsu, Yu-Kuang K.; Wang, Lin-Feng
The current study sought to further explore the theoretical model of mutual influence among therapy group members, which postulates that group members influence one another and that this influence is a key component of group treatments. However, a recent finding suggested that group members' adjusted posttreatment outcomes were not significantly related. The current study reexamined mutual influence by testing this relationship in a markedly different sample on two outcome variables, depression and hopelessness. The data consisted of 78 HIV+ men participating in six therapy groups in a Taiwanese correctional facility. Contrary to our hypothesis, the relationship between an individual group member's posttreatment depression and the aggregated depression scores of the other group members was not significant. As hypothesized, the relationship between an individual group member's posttreatment hope and the aggregated sense of hope of the other group members was significant.